Securing Blockchain Enterprises: Legal Due Diligence Amidst Rising Cyber Threats - Multazam, Mochammad Tanzil; Phahlevi, Rifqi Ridlo; Purnomo, Melati Indah; Purwaningsih, Sri Budi; Sobirov, Bobur (Faculty of Law, Universitas Padjadjaran, 2024)
This study aims to understand the vulnerabilities faced by enterprises operating on token-based blockchain businesses and the role of legal, due diligence procedures in mitigating such risks. It employed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses method and sourced data from DeFillama, a platform tracking decentralized finance developments, to categorize hacking incidents into five major groups: Ecosystem, Infrastructure, Protocol Logic, Rugpull, and Smart Contract Language. The findings highlight that Infrastructure attacks, mainly through Private Key Compromise, are the most damaging. They cause losses of over 800 million dollars between 2020 and 2023. It necessitates comprehensive and adaptable legal, due diligence strategies focusing on jurisdictional legal frameworks, platform usage terms, regulatory compliance, and potential legal issues. The study underscores the importance of further research to evaluate and enhance the effectiveness of these measures in addressing the unique challenges of blockchain technology, which are crucial for enhancing the resilience and sustainability of blockchain enterprises, thereby promoting global trust in this emerging field.DOI: https://doi.org/10.22304/pjih.v11n1.a2